Performance evaluation and finite element modeling of heat, mass, and fluid flow inside a hybrid solar dryer during drying of paddy grains - Jha, Aprajeeta; Tripathy, P. P. (Frontiers in Food Science and Technology, 2024)
A comprehensive assessment of a photovoltaic (PV) integrated hybrid solar dryer (HSD) for drying paddy was undertaken in the present investigation. Performance evaluation of the system along with finite element model of HSD at no-load and load conditions were successfully developed. Study showed that the collector efficiency at different power levels varied from 49.24% to 81.19% and was observed to be highest at thermal intensity of 750 W/m 2 . The evaporative capacity of the system was varied between 0.25-0.39 kg/h. Comparative analysis of the system efficiency, specific energy consumption (SEC) and specific moisture extraction rate (SMER) in HSD, tray dryer (TD) and mixed-mode solar dryer (MMSD) was also attempted. SEC values for HSD was observed to be approximately 72% and 46% less than TD and MMSD, respectively. It was also observed that SMER values of 0.27, 0.15 and 0.08 kg/kWh was attained in HSD, MMSD and TD, respectively. The average drying rate of paddy samples subjected to HSD was 36.36% and 84.61% higher than TD and MMSD, respectively. Moreover, the percentage of time saved during drying in a hybrid solar dryer was estimated to be 33% and 50% higher than in comparison to mixed mode solar dryer and tray dryer, respectively. Simulation results of the air distribution profile of the collector and chamber revealed the dead zone, where the air velocity tends to decrease below 0.5 m/s. It is imperative to highlight that the model contented reasonably in anticipating the temperature profile, moisture profile and air distribution pattern within the dryer at load and no-load condition. The present study affirms the suitability of PV-assisted HSD for sustainable drying of food grains.